Isolated Fetal Ascite Associated with Cardiac Diseases - Vehbi Doğan; Ayşe Hendekçi; Bilal Özelce; Şahin Takçı; Deniz Anuk İnce; Nihan Güneri Doğan (Güncel Pediatri)
Fetal ascite is defined as fluid accumulation in peritoneal cavity. It can be seen as isolated disease or an early sign of hydrops fetalis. Once fetal ascite is detected, a careful examination for hydops fetalis and possible underlying disease is necessary, since its prognosis and treatment depends mostly on the cause. Non-immunologic fetal ascite is an uncommon problem occurring for many reasons, such as urinary tract obstruction, congenital infections, genetic and metabolic diseases, gastrointestinal diseases and cardiovascular diseases. Here in this report we present two isolated fetal ascite that occurred secondary to cardiac diseases.